Phytochemical Screening of Indigofera zollingeriana Leaf Extract as Candidate Functional Ingredient in Fish Feed - Lidiawati; Darus Sa’adah J. Paransa; Deiske Adeliene Sumilat; Diane Joula Kusen; Nickson J. Kawung; Juliet Merry Eva Mamahit (JURNAL PESISIR DAN LAUT TROPIS, 2025)
This study aimed to identify the secondary metabolites in Indigofera zollengeriana leaves through phytochemical screening. The results revealed that the leaf extract contained alkaloids (+++), flavonoids (+), tannins (+), phenolics (+), and saponins (+), while steroids and triterpenoids were not detected. These phytochemical compounds possess various biological activities, including antibacterial, antioxidant, immunostimulant, and feed efficiency-enhancing properties. In aquaculture, alkaloids act as antimicrobial agents, flavonoids and phenolics reduce oxidative stress by controlling Reactive Oxygen Species (ROS), tannins support digestive health, and saponins improve nutrient absorption and pathogen control. The absence of steroids and triterpenoids adds to the safety profile, minimizing the risk of hormonal disruption and toxicity in fish. Therefore, this study highlights the potential of Indigofera leaves as a source of functional feed additives in sustainable aquaculture to enhance fish growth and health. Keywords: Indigofera zollengeriana, phytochemicals, secondary metabolites, aquaculture   Abstrak Penelitian ini bertujuan untuk mengidentifikasi kandungan metabolit sekunder pada daun Indigofera zollengeriana melalui uji skrinning fitokimia. Hasil analisis menunjukkan bahwa ekstrak daun Indigofera mengandung alkaloid (+++), flavonoid (+), tanin (+), fenolik (+), dan saponin (+), sedangkan senyawa steroid dan triterpenoid tidak terdeteksi. Kandungan fitokimia tersebut diketahui memiliki berbagai aktivitas biologis, antara lain antibakteri, antioksidan, imunostimulan, serta peningkat efisiensi pakan. Dalam konteks budidaya perikanan, alkaloid berfungsi sebagai agen antimikroba, flavonoid dan fenolik berperan dalam menekan stres oksidatif dengan mengendalikan produksi Reactive Oxygen Species (ROS), tanin mendukung kesehatan pencernaan, sementara saponin dapat meningkatkan absorpsi nutrien dan pengendalian patogen. Ketiadaan steroid dan triterpenoid menjadi nilai tambah karena mengurangi risiko efek hormonal dan toksisitas pada ikan. Dengan demikian, penelitian ini menegaskan potensi daun Indigofera sebagai sumber bahan pakan fungsional dalam akuakultur berkelanjutan untuk mendukung pertumbuhan dan kesehatan ikan. Kata kunci: Indigofera zollengeriana, fitokimia, metabolit sekunder, budidaya